Síntese estereosseletiva de tioespiro[4.n]alcanonas e reatividade de (E)-1-(3-benzilideno-2-metoxiciclohexenil)-2,2,2- trifluoretanona - Ketzer, Alex (2022)
The present thesis initially describes a methodology for obtaining two series of diastereoisomers of 1-aryl-4-hydroxy-2-thiaspiro[4,5]alkan-6-ones (5a-k and 6a-k), totaling 22 novel compounds by sulfa-Michael addition reaction. For this purpose, 1,4-dihydroxy-2,5- dithiane was used under mild reaction conditions, such as ethanol as solvent and triethylamine as a base, were used, and yields of 52 to 98% could be obtained. The influence of the size of the spiro carbocyclic portion was evaluated, by using precursor (E)-2-arylidenecyclohexanones (3a-h) and (E)-2-arylidene-cyclopentanones (3i-k) as well as the impact of different substituted aryl groups such as, phenyl, 4-methoxyphenyl, 4-nitrophenyl, 4- fluorophenyl, 4-chlorophenyl, 4-methylphenyl, 1-naphthyl, 4-(N,N)dimethylphenyl on the stereoselectivity of the reactions. The resulting compounds were fully characterized from spectroscopic analyses such as ¹H and ¹³C NMR, HSQC, HMBC, X-ray diffraction as well as mass spectrometry. A preference for the formation of the diastereoisomer (1S,4S,5S) for the cyclohexyl derivatives (a-h) and (1S,4R,5S) for the cyclopentyl derivatives (i-k) was observed. As a derivation (application), fluorination reactions by nucleophilic substitution were also carried out employing DAST. Modest yields on the order of 6 - 38% were obtained using protocols established in the literature for fluorination of tetrahydrothiophenes. After ¹H, ¹³C and ¹9F NMR spectroscopic characterization, it was found that the reaction occurred in such a way as to maintain the chiral configuration of the starting material, this feature being confirmed by X-ray diffraction. Subsequently, this thesis studied the development of the synthesis and derivatization reactions of a new model of trifluoromethyl substituted vinyl ketone, which was obtained from the acetal acylation of (E)-2-benzylidene-cyclohexanone (2a) with trifluoroacetic anhydride. Thus the structural characterization of (E)-1-(3-benzylidene-2- methoxycyclohexenyl)-2,2,2-trifluoroethanone (10) was performed by ¹H and ¹³C NMR techniques, as well as by single crystal X-ray diffraction. Additionally, the reactivity of the three possible electrophilic centers of vinyl ketone 10 were assigned from the LUMO coefficients, obtained by theoretical TD-DFT calculations. Experimental tests were carried out from nucleophilic substitution and cyclo-condensation reactions, employing primary amines, aryl and alkyl amines (04 compounds up to 95% yield); 1,2 dinucleophiles such as phenyl hydrazine, semicarbazide and thiosemicarbazide (03 compounds, up to 68% yield); and 1,3 dinucleophiles like amidines, (03 compounds up to 68% yield). All these derivatives were characterized by melting point, ¹H- and ¹³C NMR spectroscopy and HRMS analyses.